2022
DOI: 10.1101/2022.02.01.475239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread contribution of transposable elements to the rewiring of mammalian 3D genomes and gene regulation

Abstract: Transposable elements (TEs) are major contributors of genetic material in mammalian genomes. These often include binding sites for architectural proteins, including the multifarious master protein, CTCF. These TE-derived architectural protein binding sites shape the 3D genome by creating loops, domains, and compartments borders as well as RNA-DNA chromatin interactions, all of which play a role in the compact packaging of DNA in the nucleus and have the potential to facilitate regulatory function.In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…We observe both loss and gain of contact upon transposable element deletion, supporting the idea that these elements can both establish new boundaries by installing CTCF-like motifs and inhibit ancient CTCF binding sites to block contact [37]. Our results are also consistent with previous findings that specific MIR elements and tRNAs can serve as insulators [48,49], while Alu and hAT provide loop anchors [50,51], and hint that repetitive elements may work in tandem [42]. We are curious to test coordination of transposable elements as shadow loop anchors, theorized by Choudhary et al to act as redundant regulatory material supporting CTCF [37].…”
Section: Discussionsupporting
confidence: 91%
“…We observe both loss and gain of contact upon transposable element deletion, supporting the idea that these elements can both establish new boundaries by installing CTCF-like motifs and inhibit ancient CTCF binding sites to block contact [37]. Our results are also consistent with previous findings that specific MIR elements and tRNAs can serve as insulators [48,49], while Alu and hAT provide loop anchors [50,51], and hint that repetitive elements may work in tandem [42]. We are curious to test coordination of transposable elements as shadow loop anchors, theorized by Choudhary et al to act as redundant regulatory material supporting CTCF [37].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of MER81derived RELA-bound regions are species-specific (79%) indicating the ancient MER81 elements may play core NF-κB functions in a human-specific manner. Growing evidence has indicated that TEs, especially evolutionarily young TEs, act as a potent source of cis-regulatory elements, which primarily innovate regulatory programs in a species-and tissue-specific manner (Buecker and Wysocka 2012;Chuong et al 2016;Fuentes et al 2018;Todd et al 2019;Choudhary et al 2022;Du et al 2022;Kelly et al 2022;Lee et al 2022). On the other hand, ancient TEs, though few, are also able to shape regulatory landscapes through either species-specific (Notwell et al 2015) or conserved mechanisms (Lynch et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TE insertions can promote new transcription factor (TF) binding sites, as well as coopt new enhancer elements and nuclear receptor response elements. These include binding sites for architectural proteins which confer widespread contribution to the dimensionality of the genome, as have been supported in computational models and validated through CRISPR-Cas9 experiments ( Choudhary et al, 2022 ).…”
Section: Molecular Functions Of Transposable Elementsmentioning
confidence: 99%